The Influence of Ethanol Extract Graptophyllum pictum L. Griff toward Phagocytic Activity of Monocyte Exposed by Candida albicans - Atik Kurniawati (Denta Journal Kedokteran Gigi, 2018)
Background: Candidiasis is one of oral infectious disease caused by Candida albicans.The role of C. albicans as pathogen opportunistic in oral infection can affected by immune system. Phagocytosis has contributed in immune system against C. albicans infection, which is the role of monocytes. Grapthophyllum L. Griff has been proved to increase macrophage’s phagocytic activity, but the effect of violet leaves ethanol extract (EEDU) to increase monocyte’s phagocytic activity on C. albicans is unknown. Objectives: To determine the effect of violet leaves extract on monocyte’s phagocytic activity on C. albicans. Methods: This research was acted in vitro on human monocyte cell culture. There was 5 groups: negative control group, positive control group (incubated in Isoprinosine) and treatment groups was incubated in EEDU 2,5%, 5%, 10%. The percentage of activated monocytes was counted. Result: The result showed that incubation of EEDU 2,5%, 5% and 10% could increase monocyte’s phagocytic activity significantly (p<0,05) compared to control groups. The number of monocyte’s phagocytosis on C. albicans incubated with EEDU 2,5%, 5% and 10% is 65%, 60,5%, and 58,75%. The optimal concentration of EEDU to increase monocyte’s phagocytic activity was 2,5%. Conclusion: The study showed that EEDU can increase monocyte’s phagocytic activity on C. albicans.